Proceedings of the 2018 World Wide Web Conference on World Wide Web - WWW '18 2018
DOI: 10.1145/3178876.3186157
|View full text |Cite
|
Sign up to set email alerts
|

Through a Gender Lens

Abstract: Based on a large data set of emoji using behavior collected from smartphone users over the world, this paper investigates genderspecific usage of emojis. We present various interesting findings that evidence a considerable difference in emoji usage by female and male users. Such a difference is significant not just in a statistical sense; it is sufficient for a machine learning algorithm to accurately infer the gender of a user purely based on the emojis used in their messages. In real world scenarios where ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…Consistent with these attitudes, females use emoji and emoticons more frequently than males do [4,37], and young adults use them more than older adults [10,25]. Moreover, females and young people preferentially use different icons and use them for different pragmatic purposes compared to males and adults, respectively [4,5,32,34,37]. Given these welldocumented differences in usage, it is natural to ask whether, and if so to what extent, different demographic categories of social media users understand emoji use differently.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Consistent with these attitudes, females use emoji and emoticons more frequently than males do [4,37], and young adults use them more than older adults [10,25]. Moreover, females and young people preferentially use different icons and use them for different pragmatic purposes compared to males and adults, respectively [4,5,32,34,37]. Given these welldocumented differences in usage, it is natural to ask whether, and if so to what extent, different demographic categories of social media users understand emoji use differently.…”
Section: Introductionmentioning
confidence: 77%
“…In some contexts, emoji use is seen as inappropriate for males [32], and it can make adults appear incompetent [13]. Consistent with these attitudes, females use emoji and emoticons more frequently than males do [4,37], and young adults use them more than older adults [10,25]. Moreover, females and young people preferentially use different icons and use them for different pragmatic purposes compared to males and adults, respectively [4,5,32,34,37].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gender differences have been found in the use of emotions and emojis (Wolf, 2000;Chen et al, 2017), where women were found to be more likely to use those digital displays of emotion. This leads to the next section.…”
Section: Gendermentioning
confidence: 99%
“…Women evaluated emoji as clearer and more meaningful and familiar [21] and gave higher overall positive ratings when assessing the valence of emoji [34]. They were also shown to be more familiar with emoji and to use them more frequently compared to men [21,34,35]. However, other studies did not report gender differences in the interpretation of emoji when using emoji questionnaires [36].…”
Section: Neutral Facementioning
confidence: 92%